Sytuacja finansowa przedsiębiorstw przemysłowych według faz cyklu życia - Żurakowska-Sawa, Joanna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
In this paper presented the financial situation of industrial enterprises according to the phases of the life cycle. The studies included 65 companies listed on the Stock Exchange in Warsaw. The period of research covered the years 2004–2008. All group of companies in 2008. have achieved lowest profitability. With foreign capital to the greatest extent benefited the companies in the growth phase. The companies in the growth phase characterized the highest level of financial liquidity.